Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\hept{\begin{cases}x+2=\frac{1}{8}\\x+2=\frac{-1}{8}\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{-15}{8}\\x=\frac{-17}{8}\end{cases}}}\)
(4x-3)4=(4x-3)2
\(\Rightarrow\)(4x-3)4 - (4x-3)2=0
\(\Rightarrow\)(4x-3)2.[(4x-3)2-1]=0
\(\Rightarrow\)(4x-3)2-1=0:(4x-3)2
\(\Rightarrow\)(4x-3)2-1=0
\(\Rightarrow\)(4x-3)2=0+1
\(\Rightarrow\)(4x-3)2=1
\(\Rightarrow\)(4x-3)2=12
\(\Rightarrow\)4x-3=1
\(\Rightarrow\)4x=1+3
\(\Rightarrow\)x=4:4
\(\Rightarrow\)x=1
(x-1)3=125
\(\Rightarrow\)(x-1)3=53
\(\Rightarrow\)x-1=5
\(\Rightarrow\)x=5+1
\(\Rightarrow\)x=6
2x+2 - 2x=96
\(\Rightarrow\)2x. 4 - 2x=96
\(\Rightarrow\)2x . (4-1) = 96
\(\Rightarrow\)2x . 3 =96
\(\Rightarrow\)2x = 96:3
\(\Rightarrow\)2x = 32
\(\Rightarrow\)2x = 25
\(\Rightarrow\)x =5
A)
\(x^3=-125\)
\(x=-5\)
Vậy x = -5
B)
| x | = x + 1
\(\Leftrightarrow\orbr{\begin{cases}x=x+1\\x=-\left(x+1\right)\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x-x=1\\x=-x-1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}0=1\left(VN\right)\\2x=-1\end{cases}}\)
\(\Leftrightarrow x=-\frac{1}{2}\)
Vậy x = -1/2
C) \(x^2=x\)
\(\Leftrightarrow x^2-x=0\)
\(\Leftrightarrow x\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
Vậy x1 = 0 ; x2 = 1
A) x3 = -125
x = -125 : 3
x \(\approx\)-41,5
B) | x | = x + 1
\(\orbr{\begin{cases}x=x\\x=-x\end{cases}}\)
=>\(\orbr{\begin{cases}x>0\\x< 0\end{cases}}\)
C) x2 = x
x \(\varepsilon\)N
~ Hok tốt ~
a) \(5^x.5^{x-1}=5^{x+x-1}=5^{2x-1}=125\)
Mà \(5^3=125\)
Nên 2x-1=3
2x =4
x=2
ta có \(\left(2x-3\right)^2=36\)
Mà \(6^2=36\)và \(-6^2=36\)
nên 2x-3=6 hoặc 2x-3=-6
Nếu 2x-3=6=> x=9/2
Nếu 2x-3=-6=> x=-3/2
\(\Rightarrow\left(2x+3\right)^3=\left(-5\right)^3\)
\(\Rightarrow\left(2x+3\right)=-5\)
\(\Rightarrow2x=-8\)
\(\Rightarrow x=\left(-8\right):2\)
\(\Rightarrow x=-4\)
tíc mình nha
\(\left(x+1\right)^3=-125\)
\(\left(x+1\right)^3=-5^3\)
\(\Leftrightarrow x+1=-5\)
\(\Rightarrow x=-6\)
\(\left(x+1\right)^3=-125\)
\(\Leftrightarrow\left(x+1\right)^3=-5^3\)
\(\Leftrightarrow\left(x+1\right)=-5\)
\(\Leftrightarrow x=-6\)
Chúc em học tốt ~~~